Analyzing the Validity of Project-Based Learning Implementation Plans in Light Vehicle maintenance: A Comprehensive Study - Muslim Muslim; Ambiyar Ambiyar; Arwizet Karudin; Doni Tri Putra Yanto; Nuzul Hidayat; Ahmad Arif; Toto Sugiarto (Universitas Negeri Padang, 2023)
Implementation of the developed Learning Implementation Plan (LIP) will result in the risk of learning not being in line with expectations if the validity of the product is not guaranteed. Thus, this research aims to investigate the validity of developing project-based lesson plans to improve effective learning outcomes. This research is research and development with a quantitative approach using the ADDIE model procedure. To obtain product validity results, the stages used are only in the development phase. The subjects in this research were 2 expert lecturers and 3 productive teachers with expertise in light vehicle engineering, and the instrument used was a feasibility questionnaire. The findings were that the project-based LIP that was developed had an average score of 88.7% in the valid category. This study concludes that it has succeeded in developing a product in the form of a valid and usable project-based lesson plan. Carrying out learning using lesson plans that are integrated with project-based learning can be an alternative to providing more meaningful learning and have a positive impact on student development.